Correlation of actor bonds, activity links, and resources ties on enterprizes competitiveness - Husvi Isabella, Pradina; Wurjaningrum, Febriana (Opción, 2020)
This study aimed to examine the effect of company relationships with suppliers (AAR Framework) on the companies, namely Small and Medium-sized Enterprises (SMEs). Results showed that the AAR Framework which consists of actor bonds, activity links and resources ties had an influence on the companies competition. Activity link was the variable with the highest position in its influence on companies competition with the results of the T-statistic 3.048 > 1.64, followed by resources ties with the results of the T-statistic 2.112 > 1.64 and the actor bond with the T-statistic results of 2.033>1.64.